Dog Squad 2: Cat Crew - Grabenstein, Chris; Hughes, Beth (New York : Random House, 2022)
"Fred, a stray dog who became the star of the show Dog Squad, is working on a new show called Cat Crew-but when he notices the felines acting strange, he wonders if the cat crew is being electronically controlled"--
Keywords: Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Adventure stories; Television programs -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Adventure and adventurers -- Fiction; Television programs -- Fiction; Action and adventure fiction; Animal fiction